Komunikasi Terapeutik Perawat Berhubungan dengan Kepuasan Pasien - Misi Siti; Zulpahiyana Zulpahiyana; Sofyan Indrayana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
Terapeutic communications is an important component in nursing, communication between nurses and patients have a therapeutic relationship that aims to cure the patient. The establishment of good therapeutic communication creates a relationship of trust between nurses and patients. Thus, the patient felt satisﬁed and comfortable with the services provided by nurses to improve the eagerness and motivation of the patient to recover. The aim of this research was to understand the nurse’a therapeutic communication with patient’s satisfaction in Pringgodani inpatient ward in Rajawali Citra Hospital Bantul, Yogyakarta. A total sample of 57 respondents were obtained by accidental sampling and used cross sectional design. Analysis in thia study used kendall tau test. The result of this research showed that 49.1% nurse’s therapeutic communication were good and 68,4% respondents felt satisﬁ ed and kendall tau test showed p=0.003 and correlation value is r=0.37. In conclusion, there was signiﬁcant correlation between nurse’s therapeutic communication and patient’s satisfaction.